The Proof of Statistical Criteria for Hardware Virtualization-Based Rootkits Detection in Computer Systems - I. Y. Korkin (Безопасность информационных технологий, 2012)
This article is devoted to hardware virtualization-based rootkits (HVBR) detection. A statistical criterion of HVBR presence has been suggested. The criterion has been proved for theoretical correlations of processor instructions execution latency. In this paper variation series, the 2nd and 4th order moments and line of instructions execution latency have been applied.